Protein translocation into the ERGIC: an upstream event of secretory autophagy. Issue 7 (2nd July 2020) - Liu, Lei; Zhang, Min; Ge, Liang
ABSTRACT: Macroautophagy/autophagy was recently shown to regulate unconventional protein secretion through a process called secretory autophagy. How the secretory cargo selectively enters into the secretory autophagosome has been a central question. Our recent studies indicate that cargo translocation into the ER-Golgi intermediate compartment, a compartment contributing membranes to the forming autophagosome, acts as a mechanism for secretory cargo entry into the vesicle and may be an early step for secretory autophagy.